2021
DOI: 10.1016/j.jcms.2020.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of splint vs splintless technique for virtually planned orthognathic surgery: A voxel-based three-dimensional analysis

Abstract: Chapter 2: Transferring the virtual plan into the operation room 2.1 The Splint transferring method 2.1.1 The conventional splint 2.1.2 The integrated splint 2.1.3 The CAD/CAM Splint 2.2 The Surgical Navigation method 2.3 The repositioning guide 2.4 The customized surgical guide and fixation plate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 52 publications
1
21
0
Order By: Relevance
“…A total of 566 patients from 21 articles were included for this systematic review. Eleven articles had a prospective study design [ 13 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], of which five were randomized [ 31 , 34 , 36 , 37 , 38 ], four were clinical trials [ 31 , 34 , 36 , 38 ] and two were multi-center [ 34 , 38 ]. The study characteristics are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 566 patients from 21 articles were included for this systematic review. Eleven articles had a prospective study design [ 13 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], of which five were randomized [ 31 , 34 , 36 , 37 , 38 ], four were clinical trials [ 31 , 34 , 36 , 38 ] and two were multi-center [ 34 , 38 ]. The study characteristics are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen records evaluated the accuracy of PSI for the maxilla [ 13 , 31 , 32 , 33 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], out of which eight exclusively focused on non-segmental Le Fort I procedures [ 31 , 32 , 34 , 36 , 38 , 43 , 45 , 46 ] and two on non-segmental Le Fort I procedures in conjunction with the accuracy of PSI for mandibular osteotomies [ 13 , 39 ]. Six studies included mixed single and segmental Le Fort I osteotomies [ 33 , 37 , 40 , 41 , 42 ]. One of the included studies investigated exclusively segmental Le Fort I osteotomies [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10] To encounter these shortcomings of the 3D analysis, superimposition techniques have been introduced for 3D analysis of the postoperative outcome of corrective jaw surgery, orthognathic surgery. [11][12][13] These techniques facilitate registration of two consecutive uni-or multimodal scans based on a reference structure. Using mutual image information (voxel-based registration (VBR)), surface similarity (surface-based registration (SBR)), or landmark similarity (landmark-based registration (LBR)), two scans or 3D objects can be superimposed.…”
Section: Introductionmentioning
confidence: 99%
“…19,21,22 For the analysis of the surgical outcome of orthognathic surgery the anterior cranial base, including the zygomatic arches and forehead, structures unaffected by surgery, have shown to be reliable references for superimposition, 18 and are therefore often used. 22 Although superimposition has shown to be efficient and reliable for skeletal assessment of orthognathic surgery, [11][12][13] this technique has only been sparsely adopted for UA analysis. [23][24][25][26][27][28][29][30][31][32] The majority of these studies used CBCT as the imaging technique, dividing the UA into three segments using cutting planes and measuring the UA volume and CSA.…”
Section: Introductionmentioning
confidence: 99%
“…Although this is new technology, several authors have already reported improved final surgical accuracy when using VSP and patient-specific custom plates compared to VSP and stereolithographic splints. 10,11,12 The purpose of this paper is to report the senior author's experience over the past 3 years using VSP and custom patient-specific implants in orthognathic surgery cases and compare these cases to a prior cohort of orthognathic surgical patients who underwent VSP without custom plates. Most importantly, we seek to specifically describe the learning curve and technical adaptations that we have implemented both in the planning and execution phases to improve intraoperative efficiency with this new technology.…”
mentioning
confidence: 99%